Syria-Palestine: Worship and Rituals - Curtis, A. H. W. (The Oxford handbook of ritual and worship in the Hebrew Bible, 2020)
Knowledge of the religion of ancient Syria has increased significantly in recent years thanks to key archaeological discoveries. Particularly important have been those from Ras Shamra (ancient Ugarit), which may offer the best window available for an understanding of Canaanite religious beliefs and practices. Excavations have revealed structures of religious significance, such as temples, sanctuaries, and tombs, as well as numerous texts. Of special interest are those mythological texts which tell the exploits of Baal, El, and the other great gods. There are also legends, sacrifice lists, pantheon lists, and prescriptions for various rituals. Some of these, notably the legends of Keret, and of Danel and his son Aqhat, provide evidence for beliefs about the religious status and significance of the king. This material enables a more considered understanding of ideas and practices that may have impacted upon Israelite religion.